2016
DOI: 10.1161/circoutcomes.115.002372
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Healthy Heart Score and the Development of Clinical Cardiovascular Risk Factors Among Women

Abstract: Background The prevailing efforts for cardiovascular disease (CVD) prevention focused on treatment of common CVD risk factors rather than primordial prevention of risk factors through health behaviors. The previously validated Healthy Heart Score effectively predicted the 20-year risk of CVD in mid-adulthood; however, it is unknown whether this risk score is associated with clinically-relevant CVD risk factors. Methods and Results We analyzed the association between the Healthy Heart Score and incidence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…When we assessed the separate effect of the three different blocks of the MEDLIFE, the dimension that captured physical activity, social interaction, rest and conviviality was the only one showing statistically significant results, mainly due to physical activity, collective and non-collective sports. Despite the wide supporting evidence of the benefits of physical activity on cardiovascular health and mortality [ 52 60 ], we cannot rule out positive effects of other components such as napping, social interaction, or eating in company that are not usually included in other previously published scores [ 22 , 25 , 61 ]. Our findings may highlight the importance of those components in the context of a healthy Mediterranean dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…When we assessed the separate effect of the three different blocks of the MEDLIFE, the dimension that captured physical activity, social interaction, rest and conviviality was the only one showing statistically significant results, mainly due to physical activity, collective and non-collective sports. Despite the wide supporting evidence of the benefits of physical activity on cardiovascular health and mortality [ 52 60 ], we cannot rule out positive effects of other components such as napping, social interaction, or eating in company that are not usually included in other previously published scores [ 22 , 25 , 61 ]. Our findings may highlight the importance of those components in the context of a healthy Mediterranean dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the HHS results showed that the participants still significantly improved their HHS at week 4. The HHS is associated with many clinical disease risks, such as diabetes mellitus, hypertension, and hypercholesterolemia [ 37 ]. In other words, studies report that patients with higher HHS show higher incidences of such diseases [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HHS is associated with many clinical disease risks, such as diabetes mellitus, hypertension, and hypercholesterolemia [ 37 ]. In other words, studies report that patients with higher HHS show higher incidences of such diseases [ 37 , 38 ]. When we converted the HHS to 20-year CVD risk, the participants’ initial risk resulted in 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The model has been validated [7] with data from large cohorts that consist primarily of non-Hispanic white, middleaged women and men and performs best among individuals without baseline CVD risk factors. Previous findings using the Healthy Heart Score showed that women in the highest quintile (poorest behaviour's) of the Healthy Heart Score had a predicted 18.01 (14.39-22.72 [20]. Researchers are currently collecting qualitative data to better understand the clinical utility of a lifestyle-only risk assessment tool with goal of adding clinical value when used in combination with short term risk models.…”
mentioning
confidence: 99%